2006
DOI: 10.1111/j.1365-2621.2006.tb08895.x
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Poly(lactic acid) Packaging Films as Influenced by Humidity and Temperature

Abstract: ENS ENS ENS R R R R RISBO ISBO ISBO ISBO ISBO ABSTRA ABSTRA ABSTRA ABSTRA ABSTRACT CT CT CT CT: : : : : The effect of moistur The effect of moistur The effect of moistur The effect of moisturThe effect of moisture sorption on stability of poly(lactic acid) (PL e sorption on stability of poly(lactic acid) (PL e sorption on stability of poly(lactic acid) (PL e sorption on stability of poly(lactic acid) (PL e sorption on stability of poly(lactic acid) (PLA) films at food-packaging condi-A) films at food-packaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
53
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 29 publications
2
53
0
Order By: Relevance
“…The degradation mechanisms and molecular weight change of PLA over time have been reported previously for 130-mm thick films at elevated temperature and humidity [12,13]; however, there is a lack of information about the degradation characteristics for fibers. Specifically, at temperatures above the glass transition temperature, but below the melting temperature, the effect of fiber diameter on the degradation characteristics of PLA is not well studied.…”
Section: Introductionmentioning
confidence: 95%
“…The degradation mechanisms and molecular weight change of PLA over time have been reported previously for 130-mm thick films at elevated temperature and humidity [12,13]; however, there is a lack of information about the degradation characteristics for fibers. Specifically, at temperatures above the glass transition temperature, but below the melting temperature, the effect of fiber diameter on the degradation characteristics of PLA is not well studied.…”
Section: Introductionmentioning
confidence: 95%
“…Fan et al [107] showed that a tensile load and a combination tensile/vertical load enhanced NHD as traced by weight loss and molecular weight change. In the case of storage in the air, the hydrolytic degradation rate of PLA increases with relative humidity (RH) and temperature [75,114].…”
Section: Effects Of Miscellaneous Medium Parametersmentioning
confidence: 99%
“…Polylactic acid (PLA) films are of attracting, increasing interest for developing biomaterial for food packaging applications, not only because of the need to replace many petroleum-based polymers (Gontard and Guilbert, 1993), but also because of its useful physical and mechanical characteristics (Drumright et al, 2000;Auras et al, 2004;Holm et al, 2004). The performance of PLA as food packaging material is undergoing progressive improvement concerning, for example, the gas barriers and mechanical properties, as a result of recent extensive developments (Auras et al, 2003;Sinha Ray et al, 2003;Lagaron et al, 2007).…”
Section: Introductionmentioning
confidence: 95%